Early Results in Flow Diverter Sizing by Computational Simulation: Quantification of Size Change and Simulation Error Assessment - Narata, Ana Paula (2018)
BACKGROUND: Sizing of flow diverters (FDs) stent in the treatment of intracranial aneurysms is a challenging task due to the change of stent length after implantation. OBJECTIVE: To quantify the size change and assess the error in length prediction in 82 simulated FD deployments. METHODS: Eighty-two consecutive patients treated with FDs were retrospectively analyzed. Implanted FD length was measured from angiographic images and compared to the nominal sizes of the implanted device. Length change was obtained by subtracting the nominal length from the real length and dividing by the nominal length. Implanted devices were simulated on 3-dimensional models of each patient. Simulation error was obtained by subtracting real length from simulated length and dividing by the real length of the FD. Subanalysis was done using ANOVA. Statistical significance was set to P < .05, and bootstrap resampling was used. RESULTS: When assessing the length change of the FD after implantation, changes of 30% in average and up to 80% with reference to the nominal length of the device were observed. The simulation results showed a lower error of 3.52% in averagewith a maximum of 30%. Paired t-test showed nonsignificant differences between measured and real length (P=.07, with the mean of differences at 0.45 mm, 95% confidence interval [-0.950 0.038]). CONCLUSION: Nominal length is not an accurate sizing metric when choosing the size of an FD irrespective of the brand and manufacturer. Good estimation of the final length of the stent after deployment as expressed by an error of 3.5% in average.